2007
DOI: 10.1016/j.tins.2007.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Fever, febrile seizures and epilepsy

Abstract: Seizures induced by fever (febrile seizures) are the most common type of pathological brain activity in infants and children. These febrile seizures and their potential contribution to the mechanisms of limbic (temporal lobe) epilepsy have been a topic of major clinical and scientific interest. Key questions include the mechanisms by which fever generates seizures, the effects of long febrile seizures on neuronal function and the potential contribution of these seizures to epilepsy. This review builds on recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
165
1
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(175 citation statements)
references
References 86 publications
2
165
1
7
Order By: Relevance
“…However, such recovery doesn't rule out the re-emergence of epilepsy in later life. Indeed, several studies have found a significant relationship between early-life seizures and a greater risk of epilepsy in later life (Cendes & Andermann, 2002;Dubé, Brewster, Richichi, Zha, & Baram, 2007).…”
Section: Rigid and Repetitive Behavioursmentioning
confidence: 99%
“…However, such recovery doesn't rule out the re-emergence of epilepsy in later life. Indeed, several studies have found a significant relationship between early-life seizures and a greater risk of epilepsy in later life (Cendes & Andermann, 2002;Dubé, Brewster, Richichi, Zha, & Baram, 2007).…”
Section: Rigid and Repetitive Behavioursmentioning
confidence: 99%
“…"Whether epileptogenic processes occurring in the immature rodent brain are analogous directly to those in children remain largely unknown...... [However], this issue will be resolved by interventional studies using molecular targets discovered in the animal model and by aiming to prevent human epileptogenesis" [13].…”
Section: Discussionmentioning
confidence: 99%
“…The worsening of most epileptic seizures with concurring infections and the existence of febrile seizures also suggested the role of an immuno-inflammatory condition in the occurrence of epilepsy (Dube et al, 2007). Juan F. Rodriguez-Ramirez, Laura Adalid-Peralta, Gladis Fragoso, Gabriela Rosas, Gabriela Meneses, Agnes Fleury, Edda Sciutto, and Graciela Cardenas / Journal of Contemporary Immunology (2015) Vol.…”
Section: Epilepsymentioning
confidence: 98%